High School Students' Self-Efficacy through Reality Group Counseling Services Bibliocounseling Techniques - Alfianita, Desi Widya; Lasan, Blasius Boli; Setiyowati, Arbin Janu (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
Abstract: This study aims to produce a guide product that can be used by counselors in order to overcome the problem of low self-efficacy. This research and development product refers to Borg & Gall model (1983). The subjects of this research are 2 guidance and counseling experts, two bibliocounseling material expert, two learning media expert, two prospective user, and 6 students wiht low self-efficacy. The results of the assessment by experts analyzed by using the inter-rater agreement model. The developed product also be tested for effectiveness in the form of small group test. Product assesment by guidance and counseling expert obtain high validity results while assesments by bibliocounselling material experts, learning media experts, and potential users get very high validity results. The product effectiveness test conductted showed that the self-efficacy scores of the students improved.Abstrak: Penelitian ini bertujuan untuk menghasilkan suatu produk yaitu berupa panduan yang dapat dimanfaatkan oleh konselor dalam rangka mengatasi permasalahan efikasi diri siswa yang rendah. Penelitian dan pengembangan ini mengacu pada model penelitian dan pengembangan Borg & Gall (1983). Subjek pada penelitian ini adalah dua ahli bimbingan dan konseling, dua ahli materi bibliokonseling, dua ahli media pembelajaran, dua calon pengguna, dan enam orang siswa dengan efikasi diri rendah. Hasil penilaian oleh para ahli dianalisis menggunakan inter-rater agreement model. Produk yang dikembangkan juga akan diuji keefektifannya dalam bentuk uji kelompok kecil. Penilaian produk oleh ahli bimbingan dan konseling memperoleh hasil validitas tinggi sedangkan penilaian oleh ahli materi bibliokonseling, media pembelajaran serta calon pengguna mendapatkan hasil validitas sangat tinggi. Uji keefektifan produk yang dilakukan menunjukkan bahwa skor efikasi diri siswa yang dijadikan subjek mengalami peningkatan.